Finding synergies and trade‐offs when linking biodiversity and climate change through cooperative initiatives. Issue 1 (13th November 2022) - Widerberg, Oscar; Boran, Idil; Chan, Sander; Deneault, Andrew; Kok, Marcel; Negacz, Katarzyna; Pattberg, Philipp; Petersson, Matilda
Abstract: The causes and consequences of biodiversity loss and climate change are deeply intertwined. Hundreds of existing cooperative initiatives—gathering thousands of states, regions, cities, companies, civil society organisations and communities—are potentially bending the curve on biodiversity loss and tackling climate change simultaneously. More research is needed to understand if, how and under what conditions cooperative initiatives are delivering on their promises and importantly how they can contribute to both 'biodiversity positive outcomes' and 'net‐zero emissions' at the same time.